Methane reductions to moderate the global warming effects - Török, Tibor; Szabó, László Zoltán; Zsarnóczai, Sándor J. (Applied Studies in Agribusiness and Commerce, 2015)
The case-study overviews the possible reduction for the methane gas emission in order to avoid of the more global warming effects and climate change caused by the human activity at latest decades. To collect international data base is for analysing and valuing methane gas emission based on the different country-groups, emphasizing responsibility of developing countries and highly developed countries for gas emission, also the methane emission based is on the economic sectors. China and India have share 8% of China and 2% of India respectively of cumulative CO2 emissions over the period 1900-2005, the US and the EU are responsible for more than half of emissions. Based on the estimation the global gas emissions of methane in the whole world has increased by 37% for period of 1990- 2030, as four decades, and this was 0,92% annual rate growth, while the OECD has increased the methane emission by 8,5% for this period, which means 0,21% growth rate annually. Scenario in developing countries for 2013-2020 the methane gas emission reduction could have been 8200 Mt of CO2e (Equivalent) and less than 10 US dollar per ton in more cost financing. Highly developed and developing economies (last one their methane emission share 56% in 1990, estimated 66,8% in 2030) increase their economic growth by mostly fossil energy resulted in increasing also methane gas emissions. The methane gas emission can be solved by those results-based-finance forms relevant to Kyoto Protocol, which can extend in the world by financial institutions.